Domestic violence against children from the view of undegraduate nursing students - Juliana Costa Machado; Viviana Batista Viana; Vanda Palmarella Rodrigues; Rosália Teixeira de Araújo; Vilara Maria Mesquita Mendes Pires; Alba Benemérita Alves Vilela (Universidade Federal de Santa Maria, 2018)
Aim: to verify the knowledge of undergraduate nursing students regarding domestic violence against children. Method: it is a descriptive-exploratory study with a qualitative approach, carried out with 20 undergraduate nursing students. The semi-structured interview and the content analysis technique have been used for data collection. Results: domestic violence against children is practiced by the people who are closest to the family; the human rights are violated, directly affecting children's growth and development; the most well-known forms of violence are physical, verbal, psychological, sexual in addition to negligence. Final considerations: discussions about domestic violence against children are important in the professional training, considering the articulation of theory and practice for the construction of learning, and the development of skills and abilities of the future nurses in order to face this problem.